The standard difference score: a new statistic for evaluating strength and conditioning programs - Pettitt, R. W. (The Journal of Strength and Conditioning Research, 2010)
Inferential statistics help the strength and conditioning specialist to determine if a team is responding to a strength and conditioning program overall; however, such statistics do not detect unusual responses among individuals such as those who may be overtraining. This article introduces the standard difference score (SDS), a new statistic for evaluating strength and conditioning programs. The SDSs are standard scores (z score) derived from a change in a raw strength and conditioning performance score. They are simple to calculate and sort, easy to plot, and can be aggregated to detect athletes exhibiting extreme performance changes from a battery of tests. Standard difference scores, when evaluated with skewness, can be substituted for conventional exploratory statistics generated with higher end statistical software programs.